BVS: A Lightweight Forward and Backward Secure Scheme for PMU Communications in Smart Grid - Wei Ren; Jun Song; Min Lei; Yi Ren (International Journal of Digital Multimedia Broadcasting)
In smart grid, phaser measurement units (PMUs) can upload readings to utility centers via supervisory control and data acquisition (SCADA) or energy management system (EMS) to enable intelligent controlling and scheduling. It is critical to maintain the secrecy of readings so as to protect customers' privacy, together with integrity and source authentication for the reliability and stability of power scheduling. In particular, appealing security scheme needs to perform well in PMUs that usually have computational resource constraints, thus designed security protocols have to remain lightweight in terms of computation and storage. In this paper, we propose a family of schemes to solve this problem. They are public key based scheme (PKS), password based scheme (PWS) and billed value-based scheme (BVS). BVS can achieve forward and backward security and only relies on hash functions. Security analysis justifies that the proposed schemes, especially BVS, can attain the security goals with low computation and storage cost.